A beautiful noise [invention of STM and AFM]. - Goldstein, H.
The author talks to Gerd Binnig from IBM's Zurich Research Laboratory about he invented the scanning tunneling microscope (STM) and atomic force microscopy (AFM) which launched the nanotech revolution.
Keywords: AFM; IBM Zurich Research Laboratory; STM; Atomic force microscopy; Nanotechnology; Scanning tunneling microscopes; Surface features